Adding backlash to the connection elements can improve the performance of a robotic exoskeleton. (October 2020) - Shafiei, Morteza; Behzadipour, Saeed
Abstract: Kinematic mismatch between exoskeletons and human body results in excess internal forces/torques and hence discomfort as well as increase the power consumption. The connection stiffness has been shown to have potentials for minimizing the kinematic mismatch effects. However, realization of a desired stiffness in the connection element seems difficult if not impractical. In this work, adding controlled backlash to the exoskeleton-body connection is investigated as a possible solution for the kinematic mismatch challenge. A stiffness model which includes backlash parameters was formulated and identified experimentally using three male subjects on a typical lower extremity exoskeleton. A performance index which includes tracking error and user's comfort was calculated on a normal gait cycle. The impact of the backlash parameters including: type, direction and range was analyzed in detail. The impact of adding a tuned backlash to the shank is significant while it is negligible for the thigh connection. The highest performance improvement was obtained by cylindrical backlash added to the shank axial direction (97%) with a range of 15 ∘ and 13 mm . The proposed method and results are believed to be directly applicable to the optimal design of robotic exoskeletons.